THE INSECURITY PROBLEMS REFLECTED IN SARA KAYS’ THREE SONGS - Fadhilla, Hildan; Herlyna, Herlyna; Nawakwulan, Lyla (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
Insecurity is a common feeling of uncertainty experienced by many people worldwide. It is described as something usual but it is hard to be ignored. It is temporary, not permanent. It can disappear but in a short period because many things that may trigger it to arise back and stay for a while. Neighborhood, appearance, and love relationships are three causes of insecurity. In this study, the objective is to find out the insecurity problems that are reflected in three songs written and sung by Sara Kays, such as Chosen Last, Picture of You, and Bored. The theory of insecurity by Abraham Maslow is applied in this study. The writer uses a descriptive qualitative method to examine each of the discussed insecurity problems. Data from this study are collected by listening to the songs, reading the whole lyrics, and identifying a few lyrics related to the topic’s issue. The study’s results are provided in some song verses as proofs and in the form of narration paragraphs as the writer’s discussion. There are three insecurity types found per three songs. Chosen Last ties to social insecurity. Picture of You associates with body image relationship. Bored attaches to relationship insecurity.